2014
DOI: 10.1037/a0033588
|View full text |Cite
|
Sign up to set email alerts
|

Proximal relationships between PTSD symptoms and drinking among female college students: Results from a daily monitoring study.

Abstract: The self-medication hypothesis has been proposed to explain comorbidity between PTSD and drinking, whereupon problem drinking develops as an attempt to modulate negative affect and ameliorate PTSD symptoms. Studies have begun utilizing daily monitoring methodologies to refine our understanding of proximal relations between PTSD, affect, and alcohol use. 136 female college drinkers with a past history of sexual victimization and 38 female college drinkers with no past trauma history, completed electronic monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
109
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(122 citation statements)
references
References 88 publications
(122 reference statements)
12
109
1
Order By: Relevance
“…Stress was found correlated with higher craving for tobacco (McCarthy et al, 2006;Van Zundert et al, 2011) and cocaine (Preston and Epstein, 2011). Positive affect was also reported correlated with craving for tobacco Dunbar et al, 2010;Ferguson et al, 2006;O'Connell et al, 2004), alcohol (Kaysen et al, 2014), and cocaine craving (Kennedy et al, 2013).…”
Section: Intra-individual Variablesmentioning
confidence: 84%
See 1 more Smart Citation
“…Stress was found correlated with higher craving for tobacco (McCarthy et al, 2006;Van Zundert et al, 2011) and cocaine (Preston and Epstein, 2011). Positive affect was also reported correlated with craving for tobacco Dunbar et al, 2010;Ferguson et al, 2006;O'Connell et al, 2004), alcohol (Kaysen et al, 2014), and cocaine craving (Kennedy et al, 2013).…”
Section: Intra-individual Variablesmentioning
confidence: 84%
“…Alcohol studies: During pre-quit periods (or among subjects that do not want to quit), one study reported a significant positive association between craving and alcohol use in the following minutes (Ray et al, 2010), and another study with alcohol use over subsequent hours (Kaysen et al, 2014).…”
Section: Craving and Usementioning
confidence: 99%
“…In this sense, it is stated as the most frequent psychiatric comorbidities: anxiety disorders (social phobia, simple phobia and post-traumatic stress disorder) and mood disorders (depression and mania) [15,16]. Similarly, other studies of comorbidities found that women who are alcohol users have anxiety disorders and depression as the most frequent psychiatric diagnoses [17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Over the course of 2 years, a random sample of 11,544 undergraduate women was obtained from the university registrar's office and recruited through mail and email. These women were invited to complete an online screening questionnaire via email and U.S. mail to determine their eligibility for the study (described in Kaysen et al, 2014). Of the students who completed the screening survey (n = 4,342; 37.6%), 860 (20%) met the study criteria of (a) consuming four or more drinks on one occasion at least twice in the past month, and (b) either reporting no history of trauma exposure or reporting sexual victimization (at least one incident of CSA or ASA before the past 3 months) and completed an online baseline assessment.…”
Section: Participants and Proceduresmentioning
confidence: 99%